PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PDRB)PERTUMBUHAN EKONOMI DAN INFLASITERHADAP NON PERFORMING FINANCE PERBANKAN SYARIAH DI CIREBON - M Anisulfata (UIN Siber Syekh Nurjati Cirebon, 2017)
ABSTRACT The variable gross Regional domestic product, economic growth and inflation greatly affect banking world, especially in terms of the occurrence of the financing problem. This research aims to find out how big the influence of gross Regional domestic product, economic growth and inflation against the occurrence of problematic financing in Islamic banking in Cirebon. The rise in gross Regional domestic product, economic growth and inflation will have an impact on a micro and macro economy. Although the Islamic banking system does not use flowers in its business operations but because Islamic banking became an integral part of the national banking system then the Sharia banking still could not break away from the excesses of the third macro variables. The methodologyusedisexplanatory data analysisandusedescriptive quantitative approach with statistical science as his instrument. Analytical techniques used is regression analysis techniques. Research the results showed that the gross Regional domestic product partially positive effect of 0.533 against the troubled financing Islamic banking in Cirebon. This means that when the gross Regional domestic product increase so troubled financing Islamic banking in Cirebon 47.7 percent decline. With the level of significance 0.000 53.3% confidence level and thus influence the rate of gross domestic product is significantly to the financing of problematic in Islamic banking. Economic growth is partially positive effect of 0.531 against the troubled financing Islamic banking in Cirebon. Keywords: Variable Gross Regional Product, the Economic Growth and Inflation Abstrak Variabel Produk Domestik Regional Bruto, Pertumbuhan Ekonomi dan inflasi sangat mempengaruhi dunia perbankan, terutama dari segi terjadinya pembiayaan bermasalah. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh Produk Domestik Regional Bruto, Pertumbuhan Ekonomi dan inflasi terhadap terjadinya pembiayaan bermasalah di perbankan syariah di Cirebon. Naiknya Produk Domestik Regional Bruto, Pertumbuhan Ekonomi dan inflasi akan berdampak pada perekonomian mikro dan makro. Meski perbankan syariah tidak menggunakan sistem bunga dalam operasional usahanya tetapi karena perbankan syariah menjadi bagian integral dari sistem perbankan nasional maka perbankan syariah tetap tidak bisa melepaskan diri dari ekses ketiga variabel makro tersebut. Metodologi yang digunakan adalah eksplanatory data analisys dan menggunakan pendekatan kuantitatif deskriptif dengan ilmu statistik sebagai alatnya. Teknik analisis yang digunakan adalah teknik analisis regresi. Hasil penelitian menunjukkan bahwa Produk Domestik Regional Bruto secara parsial berpengaruh positif sebesar 0,533 terhadap pembiayaan bermasalah perbankan syariah di Cirebon. Artinya, ketika Produk Domestik Regional Bruto mengalami kenaikan maka pembiayaan bermasalah perbankan syariah di Cirebon mengalami penurunan 47,7 persen. Dengan tingkat signifikansi 0,000 dan tingkat kepercayaan 53,3% maka pengaruh tingkat Produk Domestik Bruto signifikan terhadap pembiayaan bermasalah di perbankan syariah. Kata Kunci: Produk Domestik Regional Bruto, Pertumbuhan Ekonomi, Inflasi, Pembiayaan Bermasalah